The Mexican War - Mills, Bronwyn; Bowman, John Stewart, 1931- (New York : Facts On File, 1992)
Chronicles the causes and events of the Mexican War, from Mexico's struggle for recognition as an independent country to the war's end in 1848.
Includes bibliographical references (p. 107) and index.
Keywords: Mexican War, 1846-1848 -- Juvenile literature; Wars -- History, 1821-1867.; Mexico